2016
DOI: 10.3354/aei00156
|View full text |Cite
|
Sign up to set email alerts
|

Assessing movement of the California sea cucumber Parastichopus californicus in response to organically enriched areas typical of aquaculture sites

Abstract: An increasing global demand for sea cucumbers has led to interest in benthic ranching of the California sea cucumber Parastichopus californicus beneath existing aquaculture sites in British Columbia, Canada, where high levels of total organic matter (TOM) are typical. The objective of the present study was to investigate movement of P. californicus in relation to areas of increased organic content to assess the feasibility of sea cucumber ranching beneath existing aquaculture sites. A laboratory experiment usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Therefore, previous studies on suspension feeders in response to flow mainly focused on their feeding behaviour and body/ appendage orientation. For sea cucumbers, most behavioural studies have been conducted on deposit-feeding species, and food availability was identified as the main factor driving movement (Navarro et al, 2014;Slater et al, 2011;van Dam-Bates et al, 2016). In the present study, water flow was shown to play an important role in eliciting displacement in C. frondosa, a freemoving suspension feeder.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore, previous studies on suspension feeders in response to flow mainly focused on their feeding behaviour and body/ appendage orientation. For sea cucumbers, most behavioural studies have been conducted on deposit-feeding species, and food availability was identified as the main factor driving movement (Navarro et al, 2014;Slater et al, 2011;van Dam-Bates et al, 2016). In the present study, water flow was shown to play an important role in eliciting displacement in C. frondosa, a freemoving suspension feeder.…”
Section: Discussionmentioning
confidence: 51%
“…Finally, they represent an economically valuable, conservation-worthy marine resource that supports coastal livelihoods around the world (Anderson et al, 2011;Purcell et al, 2013). The habitat requirements, movement patterns, population densities and broad spatial distribution of sea cucumbers have previously been linked to a variety of factors including depth (Mercier et al, 2000a;Woodby et al, 2000), substratum characteristics (Dissanayake and Stefansson, 2012;Hamel and Mercier, 1996;Mercier et al, 2000a,b;Slater and Jeffs, 2010;Woodby et al, 2000;Young and Chia, 1982), food availability (Navarro et al, 2013(Navarro et al, , 2014van Dam-Bates et al, 2016), light intensity, temperature and salinity fluctuations (Navarro et al, 2014), as well as predator pressure (Slater and Jeffs, 2010). Under most circumstances, sea cucumbers are considered sedentary or sessile, although they may move in direct response to environmental conditions (Young and Chia, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…One method would be to deploy benthic cages or fencing (Hannah et al. ), although mesh sizes required to contain small juvenile sea cucumbers would be so small (van Dam‐Bates ) they would potentially restrict water flow to the animals, especially under conditions of heavy biofouling. Those cages or fences would require regular maintenance by divers to ensure that they remained clean, a process that would be not only costly but potentially a hazard to divers operating underneath shellfish and/or finfish culture gear.…”
mentioning
confidence: 99%
“…Those cages or fences would require regular maintenance by divers to ensure that they remained clean, a process that would be not only costly but potentially a hazard to divers operating underneath shellfish and/or finfish culture gear. Also, California sea cucumbers are adept climbers, and it could be difficult to prevent their movement over the tops of fences (van Dam‐Bates ). To maximize the uptake of farm nutrients, stocking densities, and farm profitability, it would be better to ranch sea cucumbers without confinement.…”
mentioning
confidence: 99%
See 1 more Smart Citation